Getekend voor publicatie in het nieuwsblad "De Tribune". N.a.v. het uitbreken van de vogelgriep - Willemen, Kees (2003)
Getekend voor publicatie in het nieuwsblad "De Tribune". N.a.v. het uitbreken van de vogelgriep.